If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2\3 (9+x)=-5 (4-x)
We simplify the equation to the form, which is simple to understand
2\3(9+x)=-5(4-x)
Reorder the terms in parentheses
+(+18+2x)=-5*(4-x)
Remove unnecessary parentheses
+18+2x=-5+*(+4-x+)
Reorder the terms in parentheses
+18+2x=+(-20+5x)
Remove unnecessary parentheses
+18+2x=-20+5x
We move all terms containing x to the left and all other terms to the right.
+2x-5x=-20-18
We simplify left and right side of the equation.
-3x=-38
We divide both sides of the equation by -3 to get x.
x=12.666666666667
| 6+2(16-1*6)= | | SolveT=M(3+FG)forG | | D=-2y+9x-9+4y-9x+6 | | x^2-7x+90=0 | | 1(2x-1)/33 | | (x^2+4)(x^2-1)=0 | | 3-2x=5-4x | | ln^2(x)=4x | | B=-3x+9y-5y+5x-4x+6y | | 12=4x+6 | | L=-9c+4b-8b+6c-3c+6b | | 9y-5=0 | | 10+2(2x-1)=16 | | (ln^2x)=4x | | (lnx^2)=4x | | 2x^2-60x=2x^2 | | W=-5c+3c-9+4 | | z+3(2-i)=5+i | | S=-5b-3b+6-7 | | x^2+x+2.5=0 | | D=-9c+6c-8c | | 64/x=4 | | A=-7y+6y | | 0.50x+0.25(30)=21.5 | | 50+(6x-2)=180 | | B=-9x-3x | | -14(2x-10)=28 | | 4a-3=15 | | 5x+5=8x-9 | | -5p+5+6p=10 | | Ep+q=29 | | f(x+3)=x^2+5x+3 |